Quality of Sleep in Children with Epilepsy - Fahad A Bashiri; Shahid Bashir (Wolters Kluwer Medknow Publications, 2018)
Background: Sleep disorders are a common concern among pediatric epilepsy patients. This study aimed to assess the sleep quality in children with epilepsy. Subjects and Methods: The present study examined parent-reported sleep problems in 34 children (20 boys and 14 girls; age 4-14 years) with epilepsy. Children's Sleep Habits Questionnaire (CSHQ) assesses sleep patterns with 33 sleep disturbance items, and each item is rated on a 3-point scale (99 total score) that describes the frequency of the behaviors. A score of 41 was used as a cutoff for identification of poor and good sleeper. Results: Epilepsy poor sleepers (based on CSHQ score) have more sleep impairment than epilepsy good sleepers (CSHQ score) (P < 0.04), and the CSHQ subscores are as follows: night awakenings (P < 0.03), sleep duration (P < 0.04), daytime sleepiness (P < 0.04), sleep-onset delay (P = 0.02), and bedtime resistance (P = 0.02). Conclusions: Although sleep problems are known to be common among young children with epilepsy, the results of this work may provide the basis for focused studies to gain deeper understanding of sleep disturbances in this population.